Assessment of cover crop adoption and impact on weed management in Wisconsin corn‐soybean cropping systems - Guilherme Chudzik; Jose J. Nunes; Nicholas J. Arneson; Grace Arneson; Shawn P. Conley; Rodrigo Werle (Agrosystems, Geosciences & Environment)
Abstract The evolution and widespread occurrence of herbicide‐resistant weeds pose a major challenge for farmers and crop consultants across North America, warranting integrated management strategies. The adoption of cover crops offer weed suppression and soil health benefits but adds management complexity. A survey, targeting farmers and crop consultants, was conducted during the spring of 2023 to evaluate current cover crop management practices and perceptions in Wisconsin cropping systems. The survey included 26 questions across five sections: respondent profile, cover crop adoption and experience, cover crop management ahead of soybean [Glycine max (L.) Merr.], cover crop management ahead of corn (Zea mays L.), and general benefits and challenges of cover crop adoption. Farmers and crop consultants represented most respondents, influencing a total of 29,500 and 557,000 ha, respectively. Waterhemp (Amaranthus tuberculatus [Moq.] J.D. Sauer) and giant ragweed (Ambrosia trifida L.) were identified as the most troublesome weeds. Over 90% of respondents use herbicides to terminate their cover crops, and 68% of respondents agree that cover crops improved overall weed control in their farms/clients’ farms to some extent [cereal rye (Secale cereale L.) as main cover crop species]. Additionally, results demonstrate a strong consensus (85%) on cover crops positively influencing water retention, with 98% agreement on their efficacy in reducing soil erosion. Results from this survey can help guide farmers, agronomists, researchers, and policymakers with cover crop adoption, management, policies, incentives, and future research and education needs in Wisconsin and beyond to support the development of more sustainable and efficient weed and crop management strategies.